Pengembangan E-Modul Dasar Listrik dan Elektronika di Sekolah Menengah Kejuruan - Reni Putri Mayenti; Muldi Yuhendri (Jurnal Pendidikan Teknik Elektro, 2021)
Basic Electrical and Electronics Subjects are basic subjects that must be studied by students. In the implementation of learning, there is a lack of handle modules for students, so that students' learning motivation is low which has an impact on learning outcomes. The availability of adequate teaching materials will certainly increase learning motivation and make it easier for students to understand lessons. Therefore, it is necessary to have teaching materials that support the learning process in utilizing technology, one of which is by using e-modules. This research aims to produce a valid and practical e-module in the subject of basic electricity and electronics for class X TITL at SMKN 1 West Sumatra. This study uses a 4-D development model, with four stages, namely Define, Design, Develop and Disseminate. The subjects of this research trial were students of class X TITL at SMKN 1 West Sumatra. The data were collected using a validity and practicality questionnaire in the form of a Likert scale that was validated by an instrument expert lecturer. The results of the e-module development research on the distribution of the e-module validity questionnaire obtained the average percentage results on the valid criteria. In distributing the e-module practicality questionnaire, teacher respondents got the average percentage result on the practical criteria and the e-module practicality questionnaire, the students' respondents got the average percentage results on the practical criteria. The results of this study indicate that the development of e-modules made for Basic Electrical and Electronics subjects has been criticized as valid and practical.